A Community‐Engaged Assessment of Barriers and Facilitators to Rapid Stroke Treatment. Issue 6 (22nd August 2016) - Nemeth, Lynne S.; Jenkins, Carolyn; Jauch, Edward C.; Conway, Sharon; Pearlman, Adam; Spruill, Ida J.; Brown, Lynette J.; Linnen, Joyce; Linnen, Florene; Andrews, Jeannette O.
Abstract: Treatment for acute ischemic stroke must be initiated within hours of stroke symptom onset, and the sooner it is administered, the better. In South Carolina, 76% of the population can access expert stroke care, and rural hospitals may provide specialized treatment using telemedicine, but many stroke sufferers seek care too late to achieve full benefit. Using a community‐engaged approach in a southern rural community, we explored barriers and facilitators to early stroke care and implications for improvement. The Community‐Engaged Assessment to facilitate Stroke Elimination (CEASE) study was guided by a community advisory group to ensure community centeredness and local relevance. In a qualitative descriptive study, eight focus groups were conducted including 52 individuals: recent stroke survivors, family members, emergency medical personnel, hospital emergency department staff, primary care providers, and community leaders. From analysis of focus group transcripts came six themes: lack of trust in healthcare system and providers; weak relationships fueled by poor communication; low health literacy; financial limitations related to health care; community‐based education; and faith as a message of hope. A hierarchy model for improving early community‐based stroke care was developed through consensus dialogue by community representatives and the research team. This model can be used to inform a community‐partnered, stakeholder‐informed intervention to improve stroke care in a rural southern community with the goal of improving stroke education, care, and outcome. © 2016 Wiley Periodicals, Inc.